Моделювання процесу визначення величини напруженості роботи водіїв на міських автобусних маршрутах - Шапенко, Євгенія; Гульчак, Оксана (Видавництво Львівської політехніки, 2018)
The driver's activity relates to one of the most tense and relevant types of work. It is associated with a great nervous-emotional tension, requires constant stability and concentration of attention, as well as high energy consumption.
Modeling of the process for determining the volume of vehicle operation at the city business routes
Keywords: 656.132